Overlapping and Mixing Residual Herbicide Programs for Weed Control in Grain Sorghum - Olumide S. Daramola; K.B. Jeremie Kouame; Taylor Lambert; Matthew Vredenburg; Atong A. Akom (Kansas Agricultural Experiment Station Research Reports, 2025)
A strong preemergence herbicide program is an essential best management practice for multiple herbicide-resistant weeds. Palmer amaranth is a prolific seed producer that has evolved resistance to 6 herbicide sites-of-action in Kansas. The objective of this study was to evaluate the effectiveness of overlapping and mixing residual herbicide programs with different sites-of-action for weed control in grain sorghum. Results showed that preemergence herbicide treatments controlled the Palmer amaranth (97%-100%) and puncturevine (97%-99%), 15 days after application. At 43 days after treatment, Outlook + Aatrex 4L and Parallel + Aatrex 4L provided the least control of Palmer amaranth (88%) and puncturevine (61%-74%) compared to other herbicide combinations, including Bicep Lite II Magnum + Callisto, FulTime NXT + Callisto, Lumax EZ + Aatrex 4L, Lumax EZ fb Degree Xtra, Lexar EZ, Lumax EZ fb Outlook + Aatrex 4L, Outlook + Aatrex 4L and Parallel + Aatrex 4L (97%-100%). Palmer amaranth and puncturevine control with Bicep Lite II Magnum at 1.5 qt/aa + Callisto at 5 oz/a or Bicep Lite II Magnum at 1.9 qt/a + Callisto at 5 oz/a showed no differences, indicating that higher rates of Bicep Lite II Magnum in combination with Callisto did not offer additional weed control benefits compared to the lower rate. Sorghum injury ranged from 2% to 10% 15 days after treatments and was not greater than 4% 22 days after treatment, suggesting that these herbicides can be safely applied to sorghum for weed control under favorable environmental conditions. Sorghum yield was not different among the pre-emergence herbicide treatments, ranging from 87 to 98 bu/a. However, the herbicide programs that provided 88% control of Palmer amaranth are not advisable given the prolific seed-producing nature of this weed and its consequences on soil seedbank replenishment and its ability to evolve resistance to herbicides targeting multiple sites-of-action.
Keywords: grain sorghum; Palmer amaranth; residual herbicides; weed control